1999
DOI: 10.1037/1040-3590.11.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Screening Version of the Hare Psychopathy Checklist—Revised (PCL:SV): An item response theory analysis.

Abstract: was developed to complement the Psychopathy Checklist-Revised (PCL-R; R. D. Hare, 1991), and for use outside forensic settings. The PCL:SV takes less time to administer and requires less collateral information than the PCL-R. An item response theory approach was adopted to determine similarities in the structural properties of the 2 instruments and whether the PCL:SV could be regarded as a short form of the PCL-R. Eight of the 12 items in the PCL:SV were strongly parallel to their equivalent PCL-R items. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
167
1
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 46 publications
12
167
1
4
Order By: Relevance
“…Following adjustments, there were significant associations between PCL: SV and Axis II disorders, similar to those previously demonstrated in forensic samples (Cooke et al, 1999;Ullrich & Marneros, 2007). These studies have indicated that PCL-R and PCL: SV total scores correlate most strongly with antisocial, borderline, histrionic, and narcissistic scores.…”
Section: Axis II Personality Disordersupporting
confidence: 84%
See 2 more Smart Citations
“…Following adjustments, there were significant associations between PCL: SV and Axis II disorders, similar to those previously demonstrated in forensic samples (Cooke et al, 1999;Ullrich & Marneros, 2007). These studies have indicated that PCL-R and PCL: SV total scores correlate most strongly with antisocial, borderline, histrionic, and narcissistic scores.…”
Section: Axis II Personality Disordersupporting
confidence: 84%
“…In this study, persons with schizophrenia, depressive episodes, mixed anxiety and depressive disorder, generalized anxiety disorder, and phobias did not have raised psychopathy scores, corresponding to offender samples which have not demonstrated associations with affective disorders (Cooke et al, 1999;Hare, 2003). In offender samples, measures of anxiety tend to have low, negative correlations with the PCL-R.…”
Section: Psychotic Affective and Anxiety Disordersmentioning
confidence: 54%
See 1 more Smart Citation
“…The factor structure of the PCL-R as well as its' screening version, the Psychopathy Checklist: Screening Version (PCL:SV; Hart et al, 1995), consists of four facets, measuring the interpersonal (tendency to display superficial, grandiose and deceitful behaviours), affective (lack of remorse and empathy, and individuals not accepting responsibility for their own actions), impulsive lifestyle (impulsivity, irresponsibility and a lack of goals) and antisocial behavioural characteristics (poor behavioural controls, as well as adolescent and adult antisociality) of psychopaths (Cooke et al, 1999;Hill et al, 2004;Vitacco et al, 2005). Given the incorporation of impulsive behaviours into the definition of psychopathy, explicitly in the lifestyle facet, one might expect psychopaths to express enhanced levels of impulsivity when measured under experimental conditions, but the evidence for elevated impulsivity levels in this context is currently inconclusive (Kiehl et al, 2000;Verona et al, 2012;But see: LaPierre et al, 1995;Varlamov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Trata-se de uma versão compacta (screening version) do PCL-R (Cooke et al, 1999). Ela é composta de 12 itens e mostrou-se válida para a previsão de violência institucional e comunitária.…”
Section: Pcl-svunclassified